基于UG的渐开线斜齿圆柱齿轮参数化设计 - 王书贤; 汪云; 邓利军; 张王进 (Jixie chuandong)
Parametric design is to use parameters to describe sizes of parts.When the part is designed,the shape of parts is changed by modifying characteristic parameters to achieve the sizes to drive the graphics.Cylindrical involute helical gear is a part of mechanical drives in common use,because of its complex tooth profile,it is difficult to carry out parametric design.The sizes of model and the characteristic parameters are correlated by setting up relational expression,the model of cylindrical involute helical gear are generated accurately.A new gear is generated rapidly by modifying gear characteristic parameter in expression, parametric design of involute helical gear is realized,so efficiency and precision of gear design is raised greatly.